2020
DOI: 10.1088/1742-6596/1511/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of morphological changes on modified sugarcane bagasse with potassium hydroxide

Abstract: In-depth research is needed to determine the characteristics of sugarcane bagasse as biosorbent. The aims of present work to determine the morphological changes of modified sugarcane bagasse. Modified sugarcane bagasse (MSB) is made by soaking it in a KOH 0.1 N solution overnight, filtered and rinsed with distilled water and neutralized with CH3COOH 1%. After drying and sieving with a size of 60 mesh, MSB is interacted with Fe solution. The change in MSB morphology was analyzed by comparing IR spectra and SEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, at wavenumber 33747.85 cm -1, there is a broad peak at ANSB5:1 and NASB10:1, the O-H functional groups. Sunarsih et al (2020), in the FTIR results of bagasse modified with KOH, showed that at a wavenumber between 3000-3800 cm -1 , there was a vibration of the O-H functional group. These results indicate that hydrogen bonds in O-H, both intra-molecular and inter-molecular.…”
Section: Determination Of Sugarcane Bagasse Functional Groups By Ftir Analysismentioning
confidence: 98%
“…However, at wavenumber 33747.85 cm -1, there is a broad peak at ANSB5:1 and NASB10:1, the O-H functional groups. Sunarsih et al (2020), in the FTIR results of bagasse modified with KOH, showed that at a wavenumber between 3000-3800 cm -1 , there was a vibration of the O-H functional group. These results indicate that hydrogen bonds in O-H, both intra-molecular and inter-molecular.…”
Section: Determination Of Sugarcane Bagasse Functional Groups By Ftir Analysismentioning
confidence: 98%